OBJECT ORIENTED MATRICS FOR TEST CASE SELECTION A STUDY - Shivneet Singh (Innovative Research Thoughts, 2021)
A software crisis is a group of issues that have arisen during the process of creating computer programs. The failure to produce software on schedule, within budget, and meeting criteria is indicative of a software crisis. Producing high-quality software in the allotted time frame at a reasonable cost and in a way that fits the demands of the end user is the primary focus of software engineering. In this study, both classical and OO software metrics have been covered. Existing software matrix-related research has been discussed. The Levenshtein distance technique has been used to talk about slicing in this study. Applications of program slicing to certain software engineering tasks have been discussed in this work. The technique using the suggested distance mechanism has been explained. Both cases have developed slices. The corresponding matrix for that scenario has been constructed. There has been some discussion regarding the research's final results.